Hepatic Actinomycosis - Ávila,Filipa (2015)
Actinomycosis is a rare disorder caused by an anaerobic gram-positive bacillus (Actinomyces), predominantly by the Actinomyces israelii species. Only 20% of cases show an abdominal manifestation, the appendix and ileocecal valve being the most frequent locations. Definitive diagnosis is based on microbiological cultures, microscopy or macroscopy examination. Nevertheless, histological examination of the percutaneous biopsy and blood microbiological cultures are rarely positives. Preoperative diagnosis is hampered by the lack of specific clinical and imaging manifestations, which often mimic malignancy. The rate of preoperative diagnosis is less than 10%, however, the outcome is excellent, with a low mortality rate. The authors describe the case of a patient who was diagnosed with primary hepatic actinomycosis only by a histological examination of the surgical specimen of left hepatectomy extended to segments V and VIII, for suspected malignant lesion. This case demonstrates the difficulties in diagnosing hepatic actinomycosis.